Study of vitamin D levels in exclusively breastfed term infants in a tertiary care centre - M., Soumya (International Journal of Contemporary Pediatrics, 2017)
Background: Exclusive breast-feeding is recommended up to 6 months of age with all its beneficial effects on child survival. Several studies have concluded that adequate intake of vitamin D cannot be met with human milk as the sole source of vitamin D. So this study was undertaken to study the serum vitamin D levels in exclusively breastfed babies and their mothers in a tertiary care hospital. Methods: It was a prospective observational study. A minimum of 100 healthy infants born at term (38-42 weeks) and weighed >2.5kgs at birth and who were exclusively breast fed from age group 3-6 months attending the hospitals attached to J J M M C were selected for study. Approval from the ethical committee of the institution was obtained. Results: In this study there were totally 43% of males and 57% of females. Among them 14 (14%) of the infants were vitamin D deficient and 19 (19%) infants were vitamin D insufficient. And in 100 mothers studied 25 (25%) mothers were vitamin D deficient and 24 (24%) mothers were insufficient of vitamin D. The mean vitamin D level in infants was 25.72 ng/ml (±11.31ng/ml) and in mothers’ it was 22.09ng/ml (±9.17ng/ml). Conclusions: Breastfeeding might be one the contributing factors if the infant is not adequately exposed to sunlight for endogenous synthesis of vitamin D and if the mother is deplete in vitamin D levels transferring lower amount of vitamin D to infant through breast milk.